Gut microbiota of the rice and corn strains of Spodoptera frugiperda: diversity and function - Oliveira, Nathalia Cavichiolli de (2021)
The insect gut microbiota is an important factor that contributes to various aspects of the physiology and ecology of their host. In this study we tested the hypothesis that the gut-associated symbionts of Spodoptera frugiperda, an important agricultural pest, may be playing a relevant role in the process of adaptation to the host plants of genetically distinct host-adapted strains, known as corn and rice strains. To this end, we characterized the gut microbiota composition of the strains using next generation 16S rRNA sequencing by sampling larvae in field conditions, evaluating the effect of strain, host plant and population origin. We also analyzed the composition of the gut microbiota under controlled conditions, including in the latter the analysis of the hindgut. We also sought to understand the origin of the microbiota associated with the caterpillars in two ways: by assessing the microbiota present in the ingested food, and by investigating the presence of bacteria in the eggs and reproductive tissues of S. frugiperda using FISH and confocal microscopy. To explore the functional aspects of these interactions, we used a metatranscriptomic approach to profile differentially expressed genes between strains in the gut of S. frugiperda and the transcriptional profile of the bacteria associated with the strains. Finally, we also used metabolomics to compare the metabolic profile of strains fed on different food sources. We found that the composition and structure of the gut microbiota between the strains was not different in the tests performed. We found that the gut microbiota of S. frugiperda is greatly modulated by the food ingested but is not a reflex of it. Additionally, we provided indications of vertical transmission of bacteria by detecting bacteria in eggs and oocytes of S. frugiperda. At the functional level, we found a metabolically active bacterial community that functioned equally in both strains of S. frugiperda, except when the food source was the artificial diet. In contrast, we found that the strains responded differently at the transcriptional level to the ingested food. Similarly, the metabolic profile of the midgut of the strains also differed for each food source tested. Finally, our findings provide additional support for Enterococcus as a core member of the bacterial community associated with the larval gut of S. frugiperda, as this genus was found metabolically active and consistently associated with the gut of S. frugiperda under all conditions analyzed, supporting the hypothesis that Enterococcus maintain true symbiotic mutualistic relationships with S. frugiperda.